Mechanical and tribological properties of polytetrafluoroethylene reinforced by nano-ZrO2: Molecular dynamic simulation. (May 2022) - Xu, Mingkun; Wang, Tingmei; Wang, Qihua; Zhang, Xinrui; Tao, Liming; Li, Song
The mechanism of enhancing the mechanical and tribological properties of polytetrafluoroethylene (PTFE) via the addition of nano-ZrO2 was investigated by virtue of molecular dynamic (MD) simulation from an atomic level. The MD was used to explore stretch and break of molecular chains for understanding the inherent mechanism of nanocomposites. The results found that elastic modulus of PTFE and PTFE/ZrO2 were 1.42 GPa and 6.43 GPa, respectively. The average friction coefficients of PTFE and PTFE/ZrO2 were 0.168 and 0.113, respectively. Compared to PTFE, the friction coefficient of PTFE/ZrO2 decreased by 32.7%. To explore the microscopic friction mechanism, the radial distribution function, atomic concentration, and atomic velocity were simulated and interpreted accordingly during the tribological process.